[Image 36] - Smith, Captain Sir William [?ob. 1732] (My University, 1803)
Captain Sir William Smith was in the Royal Engineers.
Original drawings and paintings of Ireland and Scotland, vol 1
Shelter of large stones in the Island of Inche drawn and dedicated to memory by Sir Wm Smith in 1803.
Keywords: Inch Island; Fortification; Architectural drawings; Ireland -- Antiquities -- Pictorial works; Donegal (Ireland : County) -- Pictorial works; Inishowen Peninsula (Ireland) -- Pictorial works; Landscapes (Representations) 1800-1810